Measurement and analysis of implicit guarantees for bank debt OECD survey results - Schich, Sebastian (OECD Publishing, 2014)
Implicit guarantees of bank debt create economic costs and distortions, which is why policy makers have clearly announced their intention to rein in the value of implicit guarantees. This report identifies key findings from the responses from 35 countries to a survey on implicit guarantees. The survey shows that while authorities have not settled on the best way of measuring such guarantees, it is important to produce estimates of the value of these guarantees to facilitate the task of assessing progress in bank regulatory reform and in reducing the value of these guarantees. Whatever method is used, the value of implicit bank debt guarantees is substantial. In absolute terms, the estimated funding cost advantages can amount to about USD 10 billion on an annual basis for banking sectors in some jurisdictions and, in many cases, they are estimated to represent the equivalent of 1% of domestic GDP; in crisis situations, this value could rise to close to 3% of domestic GDP.